Analysis of the deforestation of the Peruvian Amazon: Madre de Dios - Luque-Ramos, Lourdes (2021)
The objective of this article was to systematize the evidence of deforestation and determine the main factors of forest loss in the department of Madre de Dios, Peru. A search was carried out for scientific research related to "deforestation", "Peruvian Amazon deforestation", deforestation Madre de Dios". Scientific articles published in a database of indexed journals were analyzed. A descriptive, non-experimental study design was chosen. For data collection, the document analysis technique was applied. Based on the evidence, it is concluded that the areas of most significant deforestation are concentrated in the southern Amazon, mainly in Madre de Dios.  In addition, the main factors of forest loss are illegal mining and mostly illegal agricultural activities; within these two activities, illegal mining is the cause of the highest percentage. Negative aspects such as the loss of biodiversity also prevail, contributing to climate change.